Stochastic simulation of top load test on poly(ethylene terephthalate) bottles: An experimental study on dispersion of elastic properties. Issue 34 (17th April 2021) - Nguyen, Thanh Tung; Luo, Yun‐Mei; Chevalier, Luc; Lesueur, François
Abstract: During the stretch blowing molding process, the elongation of macromolecular chains modifies the final mechanical properties of poly(ethylene terephthalate) (PET) bottle. Especially Young's modulus can be multiplied by two or more in the longitudinal direction and more than three times in the circumferential direction in the cylindrical region of the blown bottle and leads to orthotropic elastic properties. Using digital image correlation, we performed an identification process using two global tests. First, the virtual field method on a specific plane specimen with a hole, allows the identification of the Poisson's ratio. Second, the modulus is measured using a 3D digital image correlation from bottles under internal pressure. The shear modulus is then identified from the heterogeneous tension tests in the first step. Since all the induced mechanical properties exhibit dispersions, a probabilistic description of the orthotropic behavior law is managed and a stochastic simulation of the top load test is performed in order to define a confidence region for the bottle performance. The results of the simulation are validated by experimental measurements of top load tests performed on PET bottles. Abstract : From heterogeneous tension test, managed on specimen cut from blown bottles, we identify the orthotropic mechanical properties. It is then possible to manage accurate simulation of top load test and compare to the experimental deformed shape and critical load.